Atrioventricular Block Necessitating Chronic Ventricular Pacing After Tricuspid Valve Surgery in Patients With a Systemic Right Ventricle: Long-Term Follow-Up - Nederend, Marieke; Jongbloed, Monique R. M.; Kiès, Philippine; Vliegen, Hubert W.; Bouma, Berto J.; Regeer, Madelien V.; Koolbergen, Dave R.; Hazekamp, Mark G.; Schalij, Martin J.; Egorova, Anastasia D. (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with transposition of the great arteries (TGA) after an atrial switch or congenitally corrected TGA (ccTGA) are prone to systemic right ventricular (sRV) failure. Tricuspid valve (TV) regurgitation aggravates sRV dysfunction. Timely TV surgery stabilizes sRV function, yet the development of atrioventricular (AV)-conduction disturbances in the course of sRV failure can contribute to sRV dysfunction through pacing-induced dyssynchrony. This study aims to explore the incidence, timing, and functional consequences of AV-block requiring ventricular pacing after TV surgery in patients with sRV. Methods Consecutive adolescent and adult patients with an sRV who underwent TV surgery between 1989 and 2020 and followed-up at our center were included in this observational cohort study. Results The data of 28 patients (53% female, 57% ccTGA, and a mean age at surgery 38 ± 13 years) were analyzed. The mean follow-up was 9.7 ± 6.8 years. Of the remaining 22 patients at the risk of developing high degree AV-block after TV surgery, 9 (41%) developed an indication for chronic ventricular pacing during follow-up, of which 5 (56%) within 24 months postoperatively (3 prior to hospital discharge). The QRS duration, a surrogate marker for dyssynchrony, was significantly higher in patients with chronic left ventricular pacing than in patients with native AV-conduction (217 ± 24 vs. 116 ± 23 ms, p = 0.000), as was the heart failure biomarker NT-pro-BNP [2,746 (1,242–6,879) vs. 495 (355–690) ng/L, p = 0.004] and the percentage of patients with ≥1 echocardiographic class of deterioration of systolic sRV function (27 vs. 83%, p = 0.001). Of the patients receiving chronic subpulmonary ventricular pacing (n = 12), 9 (75%) reached the composite endpoint of progressive heart failure [death, ventricular assist device implantation, or upgrade to cardiac resynchronization therapy (CRT)]. Only 4 (31%) patients with native AV-conduction (n = 13) reached this composite endpoint (p = 0.027). Conclusion Patients with a failing sRV who undergo TV surgery are prone to develop AV-conduction abnormalities, with 41% developing an indication for chronic ventricular pacing during 10 years of follow-up. Patients with chronic subpulmonary ventricular pacing have a significantly longer QRS complex duration, have higher levels of the heart failure biomarker NT-pro-BNP, and are at a higher risk of deterioration of systolic sRV function and progressive heart failure.